The relative growth and sexual maturity of the freshwater crab Dilocarcinus pagei (Brachyura, Trichodactylidae) in the northwestern region of the state of São Paulo - Herrera, Daphine R. [UNESP]; Davanso, Thiago M. [UNESP]; Costa, Rogério Caetano da [UNESP]; Taddei, Fabiano G. (Fundação Zoobotânica do Rio Grande do Sul, 2013)
The aim of the present study was to determine the size at sexual maturity in the freshwater crab Dilocarcinus pagei Stimpson, 1861, from a population located in Mendonça, state of São Paulo, Brazil. The crabs were sampled monthly (July 2005 to June 2007), at Barra Mansa reservoir. The specimens were captured manually or in sieves passed through the aquatic vegetation. The crabs were captured and separated by sex based on morphology of the pleon and on the number of pleopods. The following dimensions were measured: carapace width (CW); carapace length (CL); propodus length (PL); and abdomen width (AW). The morphological analysis of the gonads was used to identify and categorize individuals according to their stage of development. The morphological maturity was estimated based on the analysis of relative growth based on the allometric equation y = ax b. The gonadal maturity was based on the morphology of the gonads by the method CW50 which indicates the size at which 50% of the individuals in the population showed gonads morphologically mature to reproduction. The biometric relationships that best demonstrated the different patterns of growth for the juvenile and adult stages were CW vs. PL for males and CW vs. AW for females (p<0.001). Based on these relationships, the estimated value to morphological sexual maturity was 21.5 mm (CW) in males and 19.7 mm (CW) in females. The determination of the size at sexual maturity and the adjustment of the data based on the logistic curve (CW50) resulted in a size of 38.2 mm for males and 39.4 mm for females (CW). Based on the data obtained for sexual maturity for D. pagei, we can estimate a minimum size for capture of 40 mm (CW). This minimum size allows at least half of the population to reproduce and retains the juveniles and a portion of the adults in the population.

Este estudo foi desenvolvido com o objetivo de determinar o tamanho da maturidade sexual de machos e fêmeas de uma população natural de Dilocarcinus pagei Stimpson, 1861 de Mendonça, São Paulo, Brasil. Os caranguejos foram coletados mensalmente (julho de 2005 a junho de 2007) na Represa Barra Mansa, capturados manualmente, ou por meio de peneiras passadas junto à vegetação aquática. Os caranguejos foram separados por sexo, de acordo com a morfologia do abdome e pleópodos. As dimensões mensuradas foram: largura da carapaça (LC); comprimento da carapaça (CC); comprimento do própodo (CP) e largura do abdome (LA). Além disso, análise morfológica das gônadas foram realizadas e caracterizadas em relação ao estágio de desenvolvimento. A maturidade morfológica foi estimada com base no estudo do crescimento relativo, esta análise é baseada na equação alométrica y = ax b e a maturidade gonadal através da morfologia das gônadas, utilizando o método LC50 indicando o tamanho em que 50% dos indivíduos encontram-se com gônadas desenvolvidas para a reprodução. As relações biométricas que melhor indicaram os diferentes padrões de crescimento das fases jovem e adulta foram LCxCP para os machos e LCxAB para fêmeas (p<0,001). Baseado nessas relações, o valor estimado para a maturidade sexual morfológica em machos foi de 21,5 mm (LC) e de 19,7 mm de (LC) para fêmeas. Na determinação da maturidade sexual gonadal, o ajuste da curva logística (LC50) resultou em um tamanho de 38,2 mm para os machos e 39,4 mm para as fêmeas (LC). Com base nos dados obtidos para a maturidade sexual é possível estimar o tamanho mínimo de captura para D. pagei de 40mm (LC), possibilitando que pelo menos metade da população consiga se reproduzir, mantendo os jovens e parte dos adultos na população.
Crescimento relativo e maturidade sexual do caranguejo dulcícola dilocarcinus pagei (brachyura, trichodactylidae) na região noroeste do estado de São Paulo
Keywords: Alometria; maturidade gonadal; maturidade morfológica; reprodução; Allometric growth; gonadal maturity; morphological maturity; reproduction